Strength and conditioning for throwing in cricket - Cronin, J. B.; Sharp, A. P.; Stronach, B.; Deuchrass, R.; Bressel, E.; Shackel, D. F.; McMaster, D. T. (Strength and Conditioning Journal, 2016)
In cricket, the ability to throw a ball at high velocity with great accuracy is critical to successful performance and often determines the outcome of matches. The skill of cricket fielding incorporates a movement phase and a pick-up and throw phase aimed at decreasing run rate or producing a run out of the opposition. A major issue in cricket is the risk of injury to players attributed to an acute spike in throwing intensity and volume during practice and matches. This article discusses strength and conditioning practices that may reduce the prevalence of throwing-related injuries and improve throwing performance.